The Effectiveness Of Marketing Strategies In Increasing Pesticide Sales Through Marketplace Platform At Bumdes Karya Maju Cemerlang In Apung Village, Tanjung Selor District, Bulungan Regency, North Kalimantan - Lejau, Novendi; Sudrartono, Tiris (Yayasan Azka Hafidz Maulana, 2025)
This study aims to evaluate the effectiveness of marketing strategies in increasing pesticide sales through the marketplace managed by BUMDes Karya Maju Cemerlang in Apung Village, Tanjung Selor District, Bulungan Regency, North Kalimantan. The marketing of pesticide products in this region is essential to support sustainable local agriculture. A qualitative method was applied through in-depth interviews and direct observations involving local farmers as the main respondents. The findings show that marketing strategies involving personal selling, social media utilization, and promotional discounts significantly impacted sales improvement. In addition, SWOT analysis revealed that strengthening cooperation with farmers and providing product training contributed to the marketing success. These findings confirm that appropriate marketing strategies rooted in farmer collaboration can enhance sales performance and strengthen BUMDes-farmer relations.